Low‐temperature synthesis of uranium monocarbide by a Pechini‐type in situ polymerizable complex method. Issue 7 (2nd February 2018) - Guo, Hangxu; Wang, Jieru; Bai, Jing; Cao, Shiwei; Chen, Denglei; Sun, Yalou; Yin, Xiaojie; Tian, Wei; Tan, Cunmin; Huang, Qing; Qin, Zhi; Deng, Qihuang
Abstract: Uranium monocarbide (UC) was successfully synthesized by the Pechini‐type in situ polymerizable complex technique (IPC) with the organic matter as the only carbon source. In the aqueous process, a mixture of citric acid (CA) and mannitol with UO 2 2 + was polymerized to form a spongy‐like organic polymeric precursor without any precipitations. The structural evolution and formation mechanism of the precursor were investigated using XRD, DSC‐TG, SEM (EDX), TEM, and FT‐IR. XRD results demonstrated that UC was obtained with the UO 2 2 + /mannitol/CA molar ratios of 1.0/0.3/1.0 at a low temperature of 1400°C. SEM and TEM analyses revealed that the UO2 nanoparticles were uniformly distributed in the carbon matrix to form UO2 /C nanocomposites, and submicrometer‐sized ellipsoidal UC particles cemented together. FT‐IR showed that a UO 2 2 + ‐CA chelated structure was firstly obtained, achieving the molecular scale mixing of uranium and C. Then the in situ charring guaranteed the intimate contact of UO2 and C, leading to a low reaction temperature in carbothermal reduction owing to a short diffusion distance.